2021
DOI: 10.1038/s41598-021-92771-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinity cycling and carbonate chemistry decoupling in seagrass mystify processes of acidification mitigation

Abstract: The adverse conditions of acidification on sensitive marine organisms have led to the investigation of bioremediation methods as a way to abate local acidification. This phytoremediation, by macrophytes, is expected to reduce the severity of acidification in nearshore habitats on short timescales. Characterizing the efficacy of phytoremediation can be challenging as residence time, tidal mixing, freshwater input, and a limited capacity to fully constrain the carbonate system can lead to erroneous conclusions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Under these particular conditions, which occurred towards the end of the tidal emersion period, any CaCO 3 precipitation was less than dissolution; precipitation may even have been impossible due to a lack of DIC substrate. In intertidal pools with a high density of Zostera marina, Miller and Kelley (2021) observed a similar decoupling between pH and a , with increases in pH not leading to an increase in saturation state at high pH values due to a lack of DIC OR CO 2− 3 . In our study, we observed even more drastic decoupling between expected changes in pH, a and NCC, with some of the fastest net dissolution rates observed at very high pH and very low a values that were a consequence of near-complete consumption of DIC by community production (Fig.…”
Section: Instances Of Aragonite Undersaturation At High Phmentioning
confidence: 63%
See 1 more Smart Citation
“…Under these particular conditions, which occurred towards the end of the tidal emersion period, any CaCO 3 precipitation was less than dissolution; precipitation may even have been impossible due to a lack of DIC substrate. In intertidal pools with a high density of Zostera marina, Miller and Kelley (2021) observed a similar decoupling between pH and a , with increases in pH not leading to an increase in saturation state at high pH values due to a lack of DIC OR CO 2− 3 . In our study, we observed even more drastic decoupling between expected changes in pH, a and NCC, with some of the fastest net dissolution rates observed at very high pH and very low a values that were a consequence of near-complete consumption of DIC by community production (Fig.…”
Section: Instances Of Aragonite Undersaturation At High Phmentioning
confidence: 63%
“…Macroalgae cultivation has been proposed as a method of bioremediation for local acidification, in particular to improve aquaculture environments (e.g., Bergstrom et al, 2019;Gao and Beardall, 2022): an increase in algal or marine plant cover would reverse or buffer the negative effects of acidification on heterotroph calcifiers. Our results and those of Miller and Kelley (2021) suggest that phytoremediation should not consider pH to be the sole indicator for "acidification remediation" and that periodical decreases in saturation state in macroalgae-or seaweed-dominated environments in summer (and during marine heat waves) may need to be considered for these proposed types of remediations.…”
Section: Instances Of Aragonite Undersaturation At High Phmentioning
confidence: 69%
“…High allochthonous and autochthonous organic carbon subsidies in seagrass meadows enhance aerobic respiration (decreasing DO%) but also stimulate anaerobic respiratory pathways in the sediment like nitrate and sulfate reduction that generate alkalinity and thereby buffer aerobic respiratory CO 2 inputs. As a result, DO and pH variations are often decoupled in seagrass meadows (Van Dam et al, 2019), especially when benthic alkalinity inputs are apparent (Miller and Kelley, 2021). Net alkalinity production in the sediments, when bottom waters are oxygenated, can occur through denitrification or through the burial of reduced products of sulfate and iron reduction (FeS x ).…”
mentioning
confidence: 99%